2005
DOI: 10.1111/j.1467-9566.2005.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

The promotion of private health insurance and its implications for the social organisation of healthcare: a case study of private sector obstetric practice in Chile

Abstract: This paper examines some of the implications of the process of privatisation of a national healthcare system for the delivery, organisation and, ultimately, the outcome of services. Through a case study of obstetric care in Chile, we illuminate the relationships between the macro-level of political decisions, the meso-level of the organisations through which government reforms were enacted, and the micro-level of clinical practice. We show that, for a significant proportion of Chilean women seeking maternity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 35 publications
0
36
0
1
Order By: Relevance
“…a stable public sector job coupled with private sector responsibilities and revenue. In an analysis of Chilean obstetricians, Murray and Elston (2005) found that dual practice was common but that obstetricians then meted out different treatment to patients depending on the patient's social status and location.…”
Section: The Role Of Medical Professionals: Practices Of Power In Repmentioning
confidence: 99%
“…a stable public sector job coupled with private sector responsibilities and revenue. In an analysis of Chilean obstetricians, Murray and Elston (2005) found that dual practice was common but that obstetricians then meted out different treatment to patients depending on the patient's social status and location.…”
Section: The Role Of Medical Professionals: Practices Of Power In Repmentioning
confidence: 99%
“…CSs are associated with an intrinsic risk of increased severe maternal outcomes compared with vaginal delivery [4][5][6]. Maternal demographic factors such as age, race, education, marital status, race/ ethnicity and other non-clinical factors like insurance status and institutional factors have been associated with and may increase the caesarean delivery rate [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Rates of CS vary according to hospital type; private hospitals have higher CS rates than do public one in both in both developed and developing countries [14][15][16]. Researchers have demonstrated the role of institutional factors such as ownership (private or public) [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colombia continued to emphasize increasing coverage through the social security strategy of SGSSS [6], while Chile had already reached universal coverage and focused on improving equity [23,24] and resolutive capacity of essential obstetric services.…”
Section: Formulation Of Maternal Care Policymentioning
confidence: 99%